OPTIMALISASI FUNGSI MANAJEMEN DALAM PEMBELAJARAN - Saprin Saprin (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2012)
Management is seen as a process or framework that involves guidance or direc-tion of a group of people toward the organizational goals or real purposes. The substances that become management studies in the process of instructional imple-mentation at school are planning, organization, actuation, and supervision. The effectiveness of the application of management function in instructional activity is indicated by the application of lesson plan principles, implementing organizati-onal actuating, and supervision functions in instructional activities.